Arts of global Africa the Newark Museum collection - Becker, Cynthia J. 1965-; Drewal, Henry John 1943-; Okeke-Agulu, Chika 1966-; Rovine, Victoria (Newark Museum, 2017)
"The Newark Museum has been at the forefront of American art museums in its representation of the arts of Africa since 1917. Newark's collection is notable for its embrace of the entire continent and its diaspora as well as for the breadth of artistic representation and inclusion of historic as well as modern and contemporary art. This catalogue is the first devoted to exploring this richly diverse collection, providing a comprehensive overview of African visual culture unmatched by most collection catalogues, ensuring its broad appeal and relevance."... Publisher's summary